Knowledge of Nurses Working in Critical Care Areas Regarding Ventilator Associated Pneumonia Prevention Bundles in a Tertiary Level Cardiac Centre - Bhandari, Sandip; Sharma, Medha; Shrestha, Gentle S (Journal of Institute of Medicine Nepal, 2021)
Introduction Prevention of ventilator associated pneumonia (VAP) is influenced by the knowledge and practices of nurses. This study was conducted to assess the knowledge of nurses working in critical care areas of a tertiary level cardiac centre regarding VAP prevention bundles. Methods In this descriptive study, 57 nurses working in critical care areas were included, they completed a self-administered questionaire containing demographic information followed by 18 multiple response questions. With the respondents choosing one or more correct answers, the percentage of correct answer for each options was obtained. For each questions, the correct percentage for all the options were averaged and expressed as average knowledge percent. The significance of association was tested using chi-square and Fisher exact test, with level of significance established at 95%. Data analysis was done using SPSS version 21. Results With a mean age of 26.8 years, the majority of the nurses had completed Bachelor’s degree (75.4%). Though 91.3% nurses had experience of more than a year in critical care, 87.7% of them had not obtained VAP or infection control training. The mean knowledge score of VAP was 70±7.5%, and 97.4% had satisfactory knowledge. There was no association between knowledge scores on prevention of VAP and educational qualification (p=0.26) and years of experience in intensive care unit (p=0.41). Conclusion Almost all of the nurses working in critical care areas had satisfactory knowledge regarding VAP bundle, however, they had lower knowledge on the definition and approach to prevent VAP. This study recommends to incorporate more nurses in training related to infection and VAP prevention.